Low-dose in situ prelocation of protein microcrystals by 2D X-ray phase-contrast imaging for serial crystallography. (2020) - Martiel, sabelle; Huang, Chia-Ying; Villanueva-Perez, Pablo; Panepucci, Ezequiel; Basu, Shibom; Caffrey, Martin
No abstract available